Influence of mean stress and stress amplitude on uniaxial and biaxial ratcheting of ST52 steel and its prediction by the AbdelKarim–Ohno model. (October 2016) - Halama, Radim; Fusek, Martin; Poruba, Zdeněk
Abstract: The paper presents a new type of experiment focused on investigation of the influence of mean stress and stress amplitude on steady state ratcheting realized in ST52 steel at the Technical University of Ostrava. Therefore, a new cyclic plasticity model based on the AbdelKarim–Ohno kinematic hardening rule, Jiang–Sehitoglu memory surface, and modified Calloch isotropic hardening rule is described. The model allows correct description of the stress–strain behavior of ST52 steel, including ratcheting, non-Masing behavior, and cyclic hardening under proportional as well as non-proportional loading. The model was implemented in the commercial FE code ANSYS using a Fortran subroutine. The results of all simulations focusing on the uniaxial and biaxial ratcheting prediction correspond with experiments very well. The AbdelKarim–Ohno nonlinear kinematic hardening rule in its original form gives an accurate prediction of ratcheting even for the non-proportional loading, when the additional hardening is correctly described by the isotropic hardening rule.